Comparative and international education survey of an infinite field - Wolhuter, Charl; Wiseman, Alexander W. 1968- (Emerald Publishing Limited, 2019)
This book explores the evolution and current state of the scholarly field of comparative and international education over 200 years of development. Experts in the field explore comparative and international education in each of the major world regions
Includes abstracts
Keywords: Geschichte; Internationaler Vergleich; Vergleichende Erziehungswissenschaft; Comparative education; Comparative education / History; International education; International education / History; Aufsatzsammlung